2007
DOI: 10.1901/jeab.2007.62-06
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Opportunity to Run Does Not Function as a Reinforcer for Mice Selected for High Daily Wheel‐running Rates

Abstract: 2Mice from replicate lines, selectively bred based on high daily wheel-running rates, run more total revolutions and at higher average speeds than do mice from nonselected control lines. Based on this difference it was assumed that selected mice would find the opportunity to run in a wheel a more efficacious consequence. To assess this assumption within an operant paradigm, mice must be trained to make a response to produce the opportunity to run as a consequence. In the present study an autoshaping procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 28 publications
3
57
0
Order By: Relevance
“…Previous studies demonstrate that the reward circuitry, including dopaminergic and endocannabinoid pathways, have been altered in HR mice. 8,10,11 Therefore, it is possible that the motivation for wheel running and sensitivity of the 'activitystat' responds differently to a WD in HR as compared with C mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrate that the reward circuitry, including dopaminergic and endocannabinoid pathways, have been altered in HR mice. 8,10,11 Therefore, it is possible that the motivation for wheel running and sensitivity of the 'activitystat' responds differently to a WD in HR as compared with C mice.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Various changes in locomotor performance, behavior and neurobiology (especially related to motivation for wheel running) have been observed in the HR lines. [10][11][12] For instance, treadmill endurance capacity is elevated in HR mice, 13 as is maximal oxygen consumption. 14 Despite the continued selection since generation 16, HR mice seem to be at a selection limit, the biological causes of which are not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed elsewhere, several lines of evidence indicate that the motivation for wheel running and/or the reward received from running has been altered in the HR lines Rhodes et al, 2005;Belke and Garland, 2007). The capacity for sustained, aerobically supported exercise has also increased in the HR lines, as demonstrated by increased endurance (Meek et al, 2009) and increases maximum oxygen consumption [V O2,max (Swallow et al, 1998b;Rezende et al, 2005;Rezende et al, 2006a)] during forced treadmill exercise.…”
Section: Introductionmentioning
confidence: 97%
“…For example, Sherwin and Nicol (1996) demonstrated that mice are motivated to engage in wheel running, even when the cost of gaining access to a wheel is increased by requiring shallow water traverses. Not only are mice apparently willing to incur a cost to gain access to a running wheel, but also operant conditioning studies have demonstrated that both rats and mice are motivated to lever press for the opportunity to run (Belke 2006;Belke and Garland 2007 (Cagniard et al 2006;Davis et al 2008;Garland et al 2011b). The interactions of these redundant neural systems are currently poorly understood (Lenard and Berthoud 2008), but it has been demonstrated in mice (Kumar et al 2010) and humans (Cai et al 2006) that food intake and physical activity, both components of energy balance, may be governed by a similar underlying genetic architecture.…”
mentioning
confidence: 99%
“…For example, Sherwin and Nicol (1996) demonstrated that mice are motivated to engage in wheel running, even when the cost of gaining access to a wheel is increased by requiring shallow water traverses. Not only are mice apparently willing to incur a cost to gain access to a running wheel, but also operant conditioning studies have demonstrated that both rats and mice are motivated to lever press for the opportunity to run (Belke 2006;Belke and Garland 2007). In addition, selective breeding for both elevated endurance capacity in rats and elevated wheel running in mice has resulted in alterations to neurobiological pathways that appear to delay the onset of exercise-induced fatigue (rats: Foley et al 2006) and increase motivation for wheel-running behavior (mice: Rhodes et al 2005).…”
mentioning
confidence: 99%